Searching for people in the workplace: aims, behaviour, and challenges - Tanja Svarre; Marianne Lykke; Ann Bygholm (Information Research: An International Electronic Journal)
Introduction. People have been shown to play an important role in solving search tasks in professional settings. Searching for a person covers a large part of the information retrieval carried out in the workplace. However, it can be challenging to identify relevant people through a query. Thus, to support workplace users, knowledge of the characteristics of people searches is needed to identify which steps can be taken to ease the retrieval process.